Reversible cerebral vasoconstriction syndrome. Issue 6 (June 2015) - Calic, Z.; Cappelen‐Smith, C.; Zagami, A. S.
Abstract Reversible cerebral vasoconstriction syndrome (RCVS) is a clinical‐radiological syndrome characterised by severe thunderclap headaches with or without other neurological symptoms and multifocal constriction of cerebral arteries that usually resolves spontaneously within 3 months. Most patients recover completely, but up to 10% have a permanent neurological disability and some even die. Previously RCVS has been described in many clinical contexts and under different names with the term RCVS first being suggested in 2007 to unify the group. The condition may be spontaneous, but in up to 60% of cases it is secondary to another cause, including vasoactive substances (medications and illicit drugs), blood products and the post‐partum state. It is believed to have a similar pathophysiological mechanism to the posterior reversible encephalopathy syndrome (PRES), and both can occur in similar clinical contexts and are frequently associated. Treatment options include calcium channel antagonists. RCVS occurs in a broad range of clinical situations making it an increasingly recognised condition about which doctors in various specialties need to be aware.